ProPublica Donors Absent From Bombshell Report on Billionaire Tax Dodgers (Washington Free Beacon, 2021)
ProPublica made waves after it obtained thousands of private tax documents for the country's wealthiest citizens and published a scathing investigation centered on the tax rates of Warren Buffett, Jeff Bezos, and Michael Bloomberg, among others. Absent from the report: any of the publication's largest donors, including Laurene Powell Jobs, David Filo, and Pierre Omidyar.